Teologi Pembebasan dalam Human Trafficking Ditinjau dari Manusia sebagai Gambar Allah dan Sila Kedua Pancasila.: Liberation Theology in Human Trafficking Seen from Man as the Image of God and the Second Precept of Pancasila - Roesmijati Roesmijati (STT KINGDOM BALI, 2022)
The case of human trafficking in Indonesia is very concerning, which is ranked in the world. Liberation theology is an attempt to carry out religious values and teaching contextually so that they can answer problems in society. One of the problems in society is the existence of human trafficking. God created humans with a high value of dignity as the image of God. Therefore, humans must respect each other. The second precept of Pancasila is written Humanity Just and Civilized, meaning that the Indonesian nation recognizes that every human being has the right to justice and treatment that upholds human values. The results of this study explain that human trafficking is contrary to the Bible, that is, humans are created as the image of God and are not by following the Indonesian philosophy of life, Pancasila, the Second Precept. This research method is a literature study/literature study method.